Contribution of polio eradication initiative to effective new vaccine introduction in Africa, 2010–2015. Issue 43 (10th October 2016) - Carole Tevi-Benissan, Mable; Moturi, Edna; Anya, Blanche-Philomene Melanga; Aschalew, Teka; Dicky, Akanmori Barthlomew; Nyembo, Poy Alain; Mbulu, Leon Kinuam; Okeibunor, Joseph; Mihigo, Richard; Zawaira, Felicitas
Highlights: Significant progress has been made to increase access to vaccines in Africa. PEI activities facilitated the noticeable progress in improving access to vaccines. PEI availed immunization with resources for new vaccine introduction. Abstract: Background: Significant progress has been made to increase access to vaccines in Africa since the 1974 launch of the Expanded Programme on Immunization (EPI). Successes include the introduction of several new vaccines across the continent and likely eradication of polio. We examined the contribution of polio eradication activities (PEI) on new vaccine introduction in the countries of the African Region. Methods: We reviewed country specific PEI reports to identify best practices relevant to new vaccine introduction (NVI), and analyzed trends in vaccine coverage during 2010–2015 from immunization estimates provided by WHO/UNICEF. Results: Of the 47 countries in African Region 35 (74%) have introduced PCV, 27 (57%) have introduced rotavirus, and 14 (30%) have introduced IPV. National introductions for HPV vaccine have been done in 5 countries, while 15 countries have held demonstration and pilot projects. In 2014, the regional coverage for the third dose of PCV (PCV3) and rotavirus vaccines was 50% and 30% respectively. By end of 2015, all countries within the meningitis belt will have introduced MenAfriVac™ vaccine. Conclusions: PEI activities had a positive effect in strengthening the process of new vaccine introduction in the African Region. The major contribution was in availing immunization funding and providing trained and experienced technical staff to introduce vaccines. More investment is needed to advocate and sustain funding levels to maintain the momentum gained in introducing new vaccines in the region.